First principles calculations and synthesis of multi-phase (HfTiWZr)B2 high entropy diboride ceramics: Microstructural, mechanical and thermal characterization. Issue 3 (March 2023) - Kavak, Sina; Bayrak, Kübra Gürcan; Mansoor, Mubashir; Kaba, Mertcan; Ayas, Erhan; Balcı-Çağıran, Özge; Derin, Bora; Öveçoğlu, M. Lütfi; Ağaoğulları, Duygu
Abstract: First principles calculations were conducted on (HfTiWZr)B2 high entropy diboride (HEB) composition, which indicated a low formation energy and promising mechanical properties. The (HfTiWZr)B2 HEBs were synthesized from the constituent borides and elemental boron powders via high energy ball milling and spark plasma sintering. X-ray diffraction analyses revealed two main phases for the sintered samples: AlB2 structured HEB phase and W-rich secondary phase. To investigate the performance of multi-phase microstructures containing a significant percentage of the HEB phase was focused in this study. The highest microhardness, nanohardness, and lowest wear volume loss were obtained for the 10 h milled and 2050 °C sintered sample as 24.34 ± 1.99 GPa, 32.8 ± 1.9 GPa and 1.41 ± 0.07 × 10 −4 mm 3, respectively. Thermal conductivity measurements revealed that these multi-phase HEBs have low values varied between 15 and 23 W/mK. Thermal gravimetry measurements showed their mass gains below 2% at 1200 °C. Graphical Abstract: ga1